2011
DOI: 10.12962/j20882033.v22i1.54
|View full text |Cite
|
Sign up to set email alerts
|

Development of Geopolymer Concrete with Different Curing Conditions

Abstract: Environmental issues resulted from cement production have become a major concern today. To develop a sustainable future it is encouraged to limit the use of this construction material that can affect the environment. Cement replacement material was proposed to partially replace cement portion in concrete. Geopolymer is a part of inorganic polymer material that has similar bonding function like cement in concrete. It consists of alkaline solutions and geological source material. Alkaline liquids used in this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…He found that the rate of strength development for ambient cured geopolymer concrete resembles that of OPC Concrete and therefore be used for onsite constructions. Similarly, Nuruddin et al (2011) found that the weight of fly ash geopolymer concrete correspond to that of OPC concrete. Analysis of microstructural properties of the specimens was shown in Fig.…”
Section: Ambient Curingmentioning
confidence: 78%
See 1 more Smart Citation
“…He found that the rate of strength development for ambient cured geopolymer concrete resembles that of OPC Concrete and therefore be used for onsite constructions. Similarly, Nuruddin et al (2011) found that the weight of fly ash geopolymer concrete correspond to that of OPC concrete. Analysis of microstructural properties of the specimens was shown in Fig.…”
Section: Ambient Curingmentioning
confidence: 78%
“…However, this method of curing is difficult to achieve for cast in situ applications. In another research Nuruddin et al (2011) prepared three separate regimes of curing, namely hot burlap curing, ambient curing, and oven curing. Geopolymer concrete specimens were produced by activating fly ash and microwave incinerated rice husk ash (MIRHA) with 8 molar solutions of sodium hydroxide solution and sodium silicate.…”
Section: Heat/oven Curingmentioning
confidence: 99%
“…The mixing process involves two stages, dry mix and wet mix [12]. Coarse aggregate, fine aggregate, and GGBS will be mixed initially in rotating pan mixer for 3 to 5 minutes.…”
Section: Mixing Of Geopolymer Concretementioning
confidence: 99%
“…According to Nuruddin et al [5] mixing process can be divided into two stages, dry mix and wet mix. Initially coarse aggregate, fine aggregate and GGBS will be mixed together in rotating pan mixer for 3 to 5 minutes.…”
Section: Mixing Of Geopolymer Concretementioning
confidence: 99%